11 Validity and reliability of an ultrasound measurement of the free length of the achilles tendon. (19th April 2018) - Barfod, Kristoffer Weisskirchner; Riecke, Anja Falk; Anders, Boesen; Hansen, Philip; Maier, Jens Friedrich; Døssing, Simon; Troelsen, Anders
Abstract : Introduction: Valid length measurements of the different segments of the Achilles tendon are needed in order to investigate if differential elongation of the Achilles tendon takes place after rupture. The purpose of this paper is to present data concerning accuracy and reliability of an ultrasound measurement of the free part of the Achilles tendon. Materials and methods: Both legs of 19 non-injured subjects were examined by MRI and ultrasound. The length from the distal tip of the soleus muscle to the tendon insertion on calcaneus was measured by three independent ultrasound examiners. Repeated ultrasound measurements were performed and compared to MRI measurements. Intra- and inter-rater reliability and the agreement between MRI and ultrasound were determined. Data were evaluated using the Intraclass Correlation Coefficient (ICC), the Standard Error of the Measurement (SEM) and the Minimal Detectable Change (MDC). Results: The measurement showed excellent intra-rater reliability (ICC 0.94 [0.91; 0.96], SEM 5 mm and MDC 13 mm) and inter-rater reliability (ICC 0.96 [0.93; 0.97], SEM 4 mm and MDC 11 mm). Ultrasound measurements on average exceeded the MRI measurements by 2 mm (n.s.); resulting in a measurement error of 5%. Conclusion: The ultrasound measurement of the free part of the Achilles tendon showed good reliability and accuracy. For comparison between groups of non-injured subjects differences of more than 5 mm can be detected. For repeated assessment of individual subject differences ≥13 mm can be detected.